Must be washed separately - Meres, Jonathan (Sydney Orchard, 2014)
The seventh hilarious title in the award-winning, laugh-out-loud series, The World of Norm. Perfect for fans of Tom Gates and Diary of a Wimpy Kid. Norm knew it was going to be one of those days when he was woken by the sound of an elephant breaking wind in the next room... Not the best start to a day, but it's about to get a whole lot worse. As if a trip to see his perfect cousins isn't bad enough, they've only gone and got the brand new Call Of Mortal Battle! Not that Norm could play anyway what with being banned off Xbox due to a curious incident of a stinky dog at bath time. Business as usual? ABSO-FLIPPING-LUTELY!!! With brilliantly funny illustrations throughout from Donough O'Malley. Praise for Jonathan Meres: 'Hilarious stuff from one of my comic heroes!' - Harry Hill 'Jonathan Meres is flipping funny!'
H
b
b